USE OF ALUMINA IN PREPARATION OF OXIME: A PRECURSOR FOR BECKMANN REARRANGEMENT - Sarkar, Sourav; Gangopadhyay, Pulak (International Journal of Current Pharmaceutical Research, 2015)
Objective: Oxime is an important precursor for many reactions like Beckmann rearrangement, oxime ether preparation etc. Oxime is generally prepared in strong acidic [1], strong basic [2] medium. Even some methods involving mild basic medium [3] is also known. But these procedures involve hazardous chemicals like inorganic acid, inorganic base, organic bases like Pyridine [4], Hyamine [5] etc. Some green methodologies have been also developed but that also involve expensive reagents like Bi2O3 [6] etc. Inthis context this work has been carried out to develop a new methodology for oxime preparation. Methods: Different oxims have been prepared in heating condition using water-ethanol medium and alumina as a base. Products have been isolated by column chromatography using 200 mesh silica gel followed by fractional crystallization. Products were verified by melting point analysis. Results: Four different aromatic oxims have been prepared in excellent yield and in an economically viable condition. Conclusion: Here preparation of oxime in a mild basic medium has been reported. Alumina (Al2O3) is pretty cheap and not mentionable hazardous and it has been used here for the first time in synthesis of oxime. Keywords: Alumina, Beckmann Rearrangement, Column Chromatography, Ethanol, Hydroxylamine Hydrochloride, Oxime, Thin Layer Chromatography.